IDENTIFICATION OF AREAS PRONE TO SEISMIC ACTIVITY OCCURRENCE USING 3D FEM NUMERICAL SIMULATIONS - Fulawka, Krzysztof; Mertuszka, Piotr; Solecki, Lech; Szumny, Marcin; Kolodziej, Roman (International Multidisciplinary Scientific GeoConference SGEM, 2024)
The seismic hazard in Polish copper mines has remained continuously at a high level, generating a relatively large number of accidents and negatively affecting the continuity of the exploitation process. To minimize the threat, a number of preventive actions are taken to reduce the ability of the rock mass to accumulate stresses, which should ultimately result in a reduction in the number and energy of seismic phenomena. Untortunately, as previous experience shows, the effectiveness of preventive measures is severely limited due to the lack of reliable information about zones of potential instability. This study presents the results of 3-dimensional numerical simulations developed in stages system, based on which attempts were made to locate zones prone to instability. The analysis was performed for a period of 10 months and the time between each stage was 1 month. For validation purposes, measurements of convergence of mining excavations were used. Then, the strength parameters of the rocks were reduced in accordance with the principles of the GSI scale so that the modelling results were as close as possible to measurements in in-situ conditions. Finally, on the basis of validated numerical models, stress concentration zones in the rock mass were determined and the calculation results were compared with the actual location of seismic phenomena in the analyzed area. Ultimately, the results of the research are the basis for stating that the use of numerical tools can significantly support the process of designing active rockburst preventive opeartions in deep underground mines.